Properties of Cement Mortars Modified with Ceramic Waste Fillers. (2015) - Jackiewicz-Rek, Wioletta; Załęgowski, Kamil; Garbacz, Andrzej; Bissonnette, Benoit
Abstract: The paper presents the results of an experimental program intended to assess the potential of sanitary ceramic waste utilization as aggregates in cement-based mortars. Their influence was evaluated with respect to workability (consistency, plasticity, pores volume), mechanical properties (compressive and flexural strength) and freeze-thaw resistance. The results showed that partial replacement of fine aggregate with sanitary ceramic fillers up to 20% of cement by weight improves compressive and flexural strength and reduces shrinkage. The test results were discussed in the lights of the literature data on influence of ceramic waste on properties of fresh and hardened concretes.